(untitled) (Historia, 2021)
Hans Endler (1871-1947), co-founder of the Conservatorium of the University of Stellenbosch in 1904, exerted a very great influence on the development of music in South Africa. However, little is known about his studies at the Conservatorium für Musik und darstellende Kunst in Vienna where he was a student from 1892 to 1897. Entries in the official documents of the Conservatorium show that Endler started studying with a backlog at 21 years of age. After working hard and having gained enough experience and confidence, he could take part as chamber music cellist in five private performances of the Conservatorium in 1897. The experience of five years of study at one of the best-known music training institutions in the world was greatly to his advantage when he came to South Africa in 1903.